Memória, protesto e festa na Parada do Orgulho LGBT de São Paulo: uma análise dialógico-discursiva - Ferreira, Rafael da Silva Marques (2020)
ABSTRACT This thesis dialogues with concrete statements produced during the first 22 editions of the São Paulo LGBT Pride Parade (1997 2018) to present an analytical reading proposal of this contemporary event, relating it, from the historical, aesthetic